An AI-based lie detector - Wang, Yuyao (Nanyang Technological University, 2025)
Deception detection is a very meaningful research direction. Traditional deception detection methods, such as those that rely on biosignals, are often problematic due to their limited accuracy, invasiveness, and susceptibility to manipulation. In contrast, deep learning-based deception detection offers a more sophisticated and flexible al-ternative. These models can analyze language patterns, voice modulations, and mul-timodal behavioral data to capture subtle clues that traditional methods may miss. In addition, deep learning models can be effectively scaled to real-world applications and better meet the requirements of modern ethical and practical standards. This makes them the best choice for reliable and robust deception detection.